Rococo drawing in eighteenth-century brazilian manuscripts: routes and expressions - Silva de Souza, Antonio Wilson (2019)
The present article considers the origins, characteristics and diffusion of the rococo, highlighting, especially, ornamentation in eighteenth-century Brazilian manuscripts. Despite the existence of stylistic studies, the peculiarities of rococo development deserve analysis that is always current and detailed, above all in order to understand better the influence that Frenchen graving exercised over the creation, development and diffusion of the style in Europe and Brazil. An emphasis on graphic ornamentation is the basis of the analysis concerning the particularities of the style, making possible a greater understanding of the significance which the design assumes as an authentic manifestation of art and allowing it to be established that the rococo became a singular reality in Brazilian artistic expression.